On Î“-TS-Acts Over Ternary Î“-Semigroups - Vasantha, Mamidipalli.; Madhusudhana Rao, D.; Siva Prasad, P.; Srinivasa Kumar, B.; Satish, T. (International Journal of Engineering and Technology, 2018)
We generalise the notion of acts over ternary semigroups to the Î“-TS-acts for a ternary Î“-semigroup T.Â  Certain intrinsic notions of Î“-TS-acts are studied.Â